2011
DOI: 10.1002/bit.23141
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Saccharomyces cerevisiae strains with enhanced ethanol tolerance by mutagenesis of the TATA‐binding protein gene and identification of novel genes associated with ethanol tolerance

Abstract: Since elevated ethanol is a major stress during ethanol fermentation, yeast strains tolerant to ethanol are highly desirable for the industrial scale ethanol production. A technology called global transcriptional machinery engineering (gTME), which exploits a mutant library of SPT15 encoding the TATA-binding protein of Saccharomyces cerevisiae (Alper et al., 2006; Science 314: 1565 Science 314: -1568, seems to a powerful tool for creating ethanol-tolerant strains. However, the ability of created strains to to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…As a screening result, only BTN2 was confirmed as the gene whose protein levels were significantly increased under severe ethanol stress so far. BTN2 encodes a v-SNARE binding protein and is associated with ethanol tolerance (Chattopadhyay and Pearce, 2002; Kama et al, 2007; Espinazo-Romeu et al, 2008; Yang et al, 2011). We first examined BTN2 mRNA level in yeast cells under severe ethanol stress (9 or 10% ethanol).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a screening result, only BTN2 was confirmed as the gene whose protein levels were significantly increased under severe ethanol stress so far. BTN2 encodes a v-SNARE binding protein and is associated with ethanol tolerance (Chattopadhyay and Pearce, 2002; Kama et al, 2007; Espinazo-Romeu et al, 2008; Yang et al, 2011). We first examined BTN2 mRNA level in yeast cells under severe ethanol stress (9 or 10% ethanol).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we focused on BTN2 whose deficiency induces hypersensitivity to ethanol (Espinazo-Romeu et al, 2008; Yang et al, 2011). BTN2 encodes a v-SNARE binding protein that is involved in intracellular protein trafficking (Kama et al, 2007) and plays a role in protein deposition in the nucleus (Miller et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire open reading frame (ORF) of SSK2 (4,740 bp) was cloned into the BamHI/SalI site of pRS316 TDH3 , a pRS316-derived plasmid harboring the TDH3 promoter (formerly described as pRS316-GCYH2gR in Yang et al 2011). However, the SSK2 ORF contains three internal BamHI sites at nucleotide (nt) 2389, 3025, and 4662 counting from the initiation codon, which should be removed without changing the reading frame.…”
Section: Cloning Of Ssk2 Open Reading Frame and Yeast Transformationmentioning
confidence: 99%
“…The technology progresses contributed significantly to the recent increase of worldwide ethanol production, from 17.0 billion liters in 2000 to more than 84.6 billion liters in 2011 (2). One of the successful strain improvement strategies was to obtain ethanol-tolerant strains from either mutant selection or more directed metabolic and genome engineering approaches and to apply them directly in industry, as ethanol is known to be highly toxic to cells (3)(4)(5)(6)(7)(8). In addition to engineering an individual gene or enzyme for better tolerance, increasing studies were recently conducted using regulatory genes or proteins as targets for ethanoltolerance improvements, as more evidences suggested that microbes tend to employ multiple resistance mechanisms in dealing with stress of single biofuel product (9,10), and the manipulation of regulatory genes could provide a route to complex phenotypes that are not readily accessible by traditional methods of targeting some number of metabolic genes (11,12).…”
mentioning
confidence: 99%